H-Infinity Control for Pitch-Roll AR.Drone - Agung Prayitno; Veronica Indrawati; Clark Arron (Universitas Ahmad Dahlan, 2016)
This paper describes the design and implementation of H-infinity controller applied to the AR.Drone to follow a given trajectory. The trajectory will be achieved by using two control signals, pitch and roll. Pitch and roll of the AR.Drone models are obtained by assuming that the transfer function of internal control for pitch and roll is the second order system. Two schemes of H-infinity controller designed for pitch and roll. H-infinity control for x-position has exogenous input of the x-reference, xref, control input of pitch value, exogenous output in the form of x-position and process output as error x. While H-infinity control for y-position has exogenous input of y-reference, yref, control input in the form of roll value, exogenous output of y-position and process output as error y. The results of simulation and implementation show that drone can follow multiple references of trajectories given.